A Longstanding, Persistent and Recurrent Case of Cryptogenic Panniculitis - Tatsiana Pukhalskaya; J. Ahmad Brown; Adam A. Sills; Bruce R. Smoller (Karger Publishers, 2020)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare subtype of cutaneous T-cell lymphoma. There may be a significant histologic overlap with traumatic panniculitis and lupus profundus. We describe a 54-year-old woman who had received a diagnosis of SPTCL based upon a left parietal scalp biopsy 5 years earlier. This diagnosis was supported by immunohistochemistry (IHC) demonstrating a CD8+ predominant lymphocyte population in the subcutis. T-cell gene rearrangement studies were not performed at that time. The patient was treated and showed significant clinical improvement. When several tender erythematous subcutaneous nodules appeared on the upper back, left plantar surface and pretibial region, repeat biopsy was performed. Histology revealed a lobular and septal panniculitis with no vasculitis. The infiltrate contained abundant eosinophils and histiocytes not seen in the original biopsy specimen. IHC demonstrated a mixture of CD4+, CD8+ and CD7+ lymphocytes with abundant CD68+ histiocytes. T-cell gene rearrangement studies performed on one of the lesions failed to demonstrate clonality. It is important to recognize that patients with SPTCL are not exempt from other types of panniculitis, and complete histologic, IHC and molecular workups are essential to properly classify all cutaneous lesions in these patients.